A Systematic Literature Review Bolted Connection Failure In Cold-Formed Steel Beam-To-Column Connection - Shamsul, Aida Syafiqah (Universiti Sains Malaysia, 2022)
This study is based on a Systematic Literature Review (SLR), in which data from previous research studies on the bolted connection failure for Cold Formed Steel (CFS) beam-to-column connections is compiled. The goal of this research is to expand on the CFS study area where its use has begun to get recognition in the construction industry. In this study, the failure mechanism of the bolted connection, the variables that influence the failure inside the bolted connection, and the tests performed on the bolted connection in CFS are described. This study focuses on the failure mechanism, influencing variables, and method utilized to determine the failure of bolted connections in CFS for beam to column connections. The results of this investigation are local buckling, bearing failure, and distortional buckling failure on the bolted connection for the CFS beam to column connection. In addition, the diameter of the bolts, the number of bolts, the bolt grade, the edge distance, and the placement of the bolts influence the failure of bolted connections in CFS beam to column connections. According to previous research, tensile testing is a popular data collection approach, whereas the Finite Element Method (FEM) utilizing ABAQUS Software is the numerical method employed.